Al-Quran Learning Through Information Processing Model Ala Joyce and Weil MTs Works in The Village Lara Mulya Baebunta District District North Luwu - Yunus, Yunus; Suardi, Dedi (Universitas Malikussaleh, 2019)
Research is executed with Actions Observational method braze (PTK). This research is executed at MTs Mulya's Opus with the subject of research student brazes VII by a total of 22 students, 1 teacher and Headmaster. Acquired Data source of that student covers, formative student essay in work problem that is given at the early cycle. Observation sheet result to measure the result step-up studies student with implemented a model of Information proceedings. Observation result and field note that gets bearing with student activity's learning on al Qur 'an happens. Observational result and the analysis concludes that deep upgrade in observational learning. 1). Proceedingses implement models models suit to arouse student information point and student studying with information yen proceedings concept has a mission to help the student to concentrate at one particular domain the which they can gain control. Observation / control, helping student develops conceptual grasp about a particular domain. 2). Learned yielding step-up student of each cycle, the which is on essays average value interest quiz 69 on 1. cycle is average value of 68.4 and on cycle IV. average value is 76.77. 3. Interference in implementation is as follows: 1) student were given by the task extant a portion out of focus little deep and serious solve that task, 2) reducings the late UNDERSTATING of material already being taught by the teacher were the caused by reducing it concentrate while word teacher.